2007
DOI: 10.1007/s00380-006-0925-1
|View full text |Cite
|
Sign up to set email alerts
|

Early sign of atherosclerosis in slow coronary flow and relationship with angiotensin-converting enzyme I/D polymorphism

Abstract: Increase in carotid artery intima-media thickness (IMT) is an early sign of atherosclerosis. Slow coronary flow (SCF) is characterized by delay of opacification of coronary arteries in coronary angiography in the absence of any evident obstructive lesion, but its etiopathogenesis remains unclear. Genes that regulate the renin angiotensin system also play a role in developing cardiovascular system disorders. The presence of deletion (D) allele in angiotensin converting enzyme (ACE) gene polymorphism is associat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0
5

Year Published

2008
2008
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 41 publications
0
13
0
5
Order By: Relevance
“…Tanriverdi et al reported that the ACE I/D polymorphism correlated with carotid intima–media thickness, which is a sign of subclinical atherosclerosis 11. These findings suggest that endothelial dysfunction and diffuse atherosclerosis may play a role in the pathogenesis of CSF.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Tanriverdi et al reported that the ACE I/D polymorphism correlated with carotid intima–media thickness, which is a sign of subclinical atherosclerosis 11. These findings suggest that endothelial dysfunction and diffuse atherosclerosis may play a role in the pathogenesis of CSF.…”
Section: Discussionmentioning
confidence: 95%
“…Serum ACE activity is higher in subjects with deletion/deletion (D/D) alleles than in subjects with I and D alleles and is related to hypertension and cardiovascular disease 8,9. The frequency of the DD genotype and D allele was reported to be higher in SCF patients 10,11…”
Section: Introductionmentioning
confidence: 99%
“…The endothelium plays a crucial role for initiation of atherosclerosis in early stage. Endothelial dysfunction was considered as early marker of atherosclerosis (21, 22). In this study, the FMD was significantly lower in slow flow group than in control and low FMD were independently related with slow coronary flow in regression analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Muitos estudos clínicos relataram a eficácia de agentes que inibem a atividade da ECA e de receptores da angiotensina II, no tratamento da aterosclerose. 80,40 A ativação do sistema renina-angiotensina-aldosterona (SRAA)…”
Section: Percentuais Dos Genótipos Entre As Raçasunclassified
“…constitui-se num fator de risco para processos de desenvolvimento da aterosclerose. 80,40 A angiotensina II age nos receptores AT1 e AT2. A estimulação dos receptores AT1 está associada à disfunção endotelial, principalmente como conseqüência de um aumento na produção de espécies reativas de oxigênio, vasoconstrição, ativação plaquetária, maior liberação do fator inibidor da ativação do plasminogênio tipo 1 (PAI-1).…”
Section: Percentuais Dos Genótipos Entre As Raçasunclassified